Pengaruh Inflasi dan Nilai Tukar terhadap Indeks Saham Syariah Indonesia (ISSI) Sebelum dan Sesudah Pemilu 2024 - Mariam, Siti; Junaedi, Dedi; Novita, Evi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study analyzes the impact of inflation and exchange rates on the Indonesia Sharia Stock Index (ISSI) before and after the 2024 Election. Using daily time series data and t-tests, the results show that inflation had a significant negative effect on ISSI before the election, but no significant effect afterward. The exchange rate had a significant negative effect in both periods, with a stronger impact after the election. These findings indicate that the 2024 Election influenced ISSI’s sensitivity to macroeconomic variables and reflect increased investor confidence and greater stability in the sharia stock market post-election. Keywords: Inflation, Exchange Rate, Indonesia Sharia Stock Index (ISSI), 2024 Election, Sharia Stock Market.